Development Strategy of Pedagogical Competence to Improve Professionalism of Islamic Education Teacher - Lukman Hakim (Jurnal Pendidikan Islam, 2017)
The purpose of this study is to analyze the pedagogical competence of PAI (Pendidikan Agama Islam/ Islamic education) teachers, the school’s strategies to develop PAI teacher’s pedagogical competence, the factors that inhibit school strategies, and the evaluation conducted by SMAN 3 (Sekolah Menengah Atas Negeri /Senior High School) 3 Tasikmalaya, Indonesia toward the implementation of the strategies. The research method used is qualitative descriptive which reveals phenomenon holistically and contextually. Data were collected by observation, interview, and documentation. Qualitative descriptive data were analyzed by arranging and classifying the data, thus providing a real picture to the reader. The study conclude that the teachers had already good pedagogical competence, like the ability to understand the diversity of learners, to prepare lesson plans and strategies, to create active, creative, effective, and fun learning, and to evaluate students’ learning outcomes.  The school had employed strategy to develop PAI teacher’s pedagogical competence such as developing teachers regularly every month, involving teachers in various scientific activities, improving the welfare of teachers and educational facilities, supervising, monitoring and evaluating the performance of teachers by providing guidance, giving rewards to outstanding teachers. Thus, the factors inhibited the teachers’ pedagogical competence development were two kinds, internal and external factor.